Contemporary India - Bahadur, Kalim 1936-.; Paul, Madan C. (Madan Chandra) 1955-.; Chakravarti, S. R.; Netaji Academy of Sub-Continental Studies (New Delhi Authorspress, 2000)
Contributed seminar papers.
"Under the auspices of Netaji Academy of Sub-Cntinental Studies."
Keywords: Political parties -- India; India -- Politics and government -- 1977-.; India -- Economic conditions -- 1947-.; India -- Social conditions -- 1947-.